Memberdayakan Rencana Detail Tata Ruang (RDTR) Kawasan Strategis Hutan Lindung Sungai Wain dan Sungai Manggar Tahun 2015-2035 dalam Mereduksi Ancaman Kelestarian Lingkungan - Adam Maulana (Jurnal Wilayah dan Lingkungan, 2016)
Protected forest is a strategic area with functions to protect biodiversity and macroclimate and to balance water use. The Act No. 12 Year 2012 provides a basis for detailing Balikpapan City spatial plan from general a spatial plan (RTRW) to detailed spatial (RDTR). As a strategic area, it carries out socio-cultural and environmental perspectives covering three strategic areas, i.e. protected, education, and settlement in the water areas. Sustainable development concept which focuses on balancing environmental, social, and economic aspects has become a macro approach for preparing the detailed plan for those three strategic areas. Currently, the protected forest areas of Wain River and Manggar River are endangered due to land use change and coal mining industry around. This article aimed to determine the development plan guidance for the protected forest areas in order to reduce the future impacts. The analysis conducted by comparing the spatial plan of protected area forest in Balikpapan to sustainable development indicators developed by the Commission of Sustainable Development United Nations. The results revealed that the management of protected forest areas conducted through the concept of "developmental conservation". This concept was conducted through collaborative role between the government as the regulator for the development of the natural attraction activity and the local communities as the main stakeholder in tourism development. The concept of sustainable development can provide the protection and preservation of the protected forest as well as the generation of economic value for local communities and the government.